1999
DOI: 10.1176/jnp.11.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Manifestations of Multiple Sclerosis

Abstract: The range of neuropsychiatric symptoms in multiple sclerosis (MS) has not been prospectively assessed. The authors, working at a tertiary medical center in Mexico City, used the Neuropsychiatric Inventory (NPI) to evaluate neuropsychiatric symptoms prospectively in 44 MS patients who were stable between relapses and 25 control subjects of similar age, education, and cognitive function. Neuropsychiatric symptoms were present in 95% of patients and 16% of control subjects. Changes present were depressive symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
1
19

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(118 citation statements)
references
References 27 publications
3
95
1
19
Order By: Relevance
“…Diaz-Olavarrieta et al [7] evaluated 44 MS patients who were stable between relapses and found neuropsychiatric symptoms in 95% of them, the most common being depression (79%), agitation (40%), anxiety (37%), irritability (35%), apathy (20%), euphoria (13%), disinhibition (13%), hallucinations (10%), aberrant motor behavior (9%), and delusions (7%). Asghar-Ali et al [8] described two patients, without a previous history of psychiatric disorders, were first thought to have bipolar disorder, but were diagnosed as MS after brain MRI and CSF examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Diaz-Olavarrieta et al [7] evaluated 44 MS patients who were stable between relapses and found neuropsychiatric symptoms in 95% of them, the most common being depression (79%), agitation (40%), anxiety (37%), irritability (35%), apathy (20%), euphoria (13%), disinhibition (13%), hallucinations (10%), aberrant motor behavior (9%), and delusions (7%). Asghar-Ali et al [8] described two patients, without a previous history of psychiatric disorders, were first thought to have bipolar disorder, but were diagnosed as MS after brain MRI and CSF examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Les travaux de plusieurs chercheurs témoignent entre autres d'un risque suicidaire accru ainsi que d'une association de la maladie avec les troubles dépressifs, anxieux, bipolaires et psychotiques (Beiske et al, 2008;Diaz-Olavarrieta, Cummings, Velazquez, & Garcia de al Cadena, 1999;Korostil & Feinstein, 2007;Patten, Svenson, & Metz, 2005;Turner, Williams, Bowen, Kivlahan, & Haselkom, 2006). La SEP a aussi une incidence certaine entre autres sur l'employabilité ainsi que sur les relations familiales.…”
Section: Sommaireunclassified
“…Les manifestations de l'anxiété en lien avec la SEP font l'objet d'un plus faible nombre d'études, mais elles ont été diagnostiquées chez 44,3 % d'un échantillon français (Chahraoui et al, 2008), chez 37 % de patients d'une clinique SEP au Mexique (Diaz-Olavarrieta et al, 1999) et chez près de 20 % d'un échantillon norvégien (Beiske et al, 2008). La prévalence de l'anxiété est de 37,5 % à vie et de 14 % au moment d'une étude effectuée auprès d'un échantillon canadien de personnes atteintes de SEP (Korostil & Feinstein, 2007).…”
Section: L'edss (Expanded Disabilityunclassified
“…It usually becomes evident in patients in their 20s or 30s. Depression, mania, and psychotic symptoms are common neuropsychiatric sequelae [63][64][65] and may result from the interruption of the integrity of frontotemporal circuits by demyelinating lesions. Psychoses can occur in patients with MS, and treatment of these psychoses is probably warranted.…”
Section: Multiple Sclerosismentioning
confidence: 99%